Learner Autonomy Through the Use of ChatGPT by Third-Year Students of English Faculty at University of Foreign Language Studies (UFLS) - Thuan Phung Tan; Thao Tran Ngo Hanh; Giang Nguyen Hoang Huong (LP. Ma'arif Janggan Magetan, 2024)
This study aimed to investigate the impact of utilizing ChatGPT on learner autonomy of third-year students of Faculty of English at the University of Danang – University of Foreign Language Studies (UD – UFLS). In this research, quantitative methods were employed with a close-ended questionnaire aiming to figure the relationship between student use of ChatGPT and their autonomy. Learner autonomy, in this study, was examined in two aspects, study habits and independence of learning. The survey involved 103 students; the collected data were analyzed statistically to answer the research questions. The study’s results showed that ChatGPT has little impact on the participants’ learning autonomy. However, this tool can be useful for learners’ study habits thanks to its personalized feedback and recommendations. Although our research has provided more insights into the field of technology-assisted language learning, especially learning with the use of ChatGPT, further research on the relationship of learning autonomy and ChatGPT with a larger sample and in a longer time should be conducted to ensure consistency and reliability of the impacts of ChatGPT on learner autonomy.